Is embellishing UCAS personal statements accepted practice in applications to medicine and dentistry?. (July 2013) - Kumwenda, Ben; Dowell, Jon; Husbands, Adrian
<x xml:space="preserve">Abstract</x> Background: The assessment of non-academic achievements through the personal statement remains part of the selection process at most UK medical and dental schools. Such statement offers applicants an opportunity to highlight their non-academic achievements, but the highly competitive nature of the process may tempt them to exaggerate their accomplishments. The challenge is that selectors cannot discern applicants' exaggerated claims from genuine accounts and the system risks preferentially selecting dishonest applicants. Aim: To explore the level and perception of deception on UCAS personal statements among applicants to medical and dental schools. To investigate the association between attitudes towards deception and various other demographic variables and cognitive ability via the UKCAT. Methods: An online survey was completed with first year students from six UK medical schools and one dental school. Questionnaire items were classified into three categories involving individual acts, how they suspect their peers behave, and overall perceptions of personal statements to influence the selection process. Descriptive statistics were used to investigate responses to questionnaire items. t-Tests were used to investigate the relationship between items, demographic variables and cognitive ability. Results: Candidates recognized that putting fraudulent information or exaggerating one's experience on UCAS personal statement was dishonest; however there is a widespread belief that their peers do it. Female respondents and those with a higher UKCAT score were more likely to condemn deceptive practices. Conclusion: The existing selection process is open to abuse and may benefit dishonest applicants. Admission systems should consider investing in systems that can pursue traceable information that applicants provide, and nullify the application should it contain fraudulent information.